Efficient Phosphorus Removal from Wastewater by a Newly Isolated Bacterium under High Salinity Condition - Deng, Ruonan; Qian Chen; Ni, Jinren (Acta Scientiarum Naturalium Universitatis PekinensisActa Scientiarum Naturalium Universitatis Pekinensis, 2013)
A bacterium capable of phosphorus removal was isolated. Through morphology observation and 16S rRNA gene sequence analysis, the isolate was identified as Salinivibrio sp. (named HG-1). Salinity tolerance and phosphorus removal efficiency under different salinity conditions of the strain were further investigated. The results showed that HG-1 grew well with the salt content varying from 1% to 13% and achieved the highest phosphorus removal efficiency under salt content of 3%. Furthermore, the single-factor and orthogonal experiment results indicated that the optimal phosphorus removal performance was obtained under the conditions with an initial pH of 6.5-7.0, C/N ratio of 9, temperature of 30°C and inoculation ratio of 10%. Under such a condition, the phosphorus removal efficiency could reach 100% in 24 hours. The strain HG-1 can independently complete phosphorus removal process, and thus could provide a novel and promising alternative for biological phosphorus removal under high salinity conditions.筛选出一株能够高效除磷的耐盐菌株HG-1。通过个体形态、菌落特征的观察和16S rRNA基因的序列分析, 初步鉴定为盐弧菌属(Salinivibrio sp.)。对菌株HG-1的耐盐性能及其在不同盐度下对磷酸盐的去除效果进行考察, 结果表明菌株对盐度的耐受范围为1%~13%, 最适盐度为3%。进一步的单因素和正交实验表明, 4个环境因素对菌株HG-1磷酸盐去除率影响的强弱为: pH>碳氮比>温度>接种量, 最优的除磷条件为pH 6.5~7.0, 温度30℃, 接种量10%, 碳氮比9, 在该条件下菌株在24小时内对磷酸盐的去除率可达100%。 将该菌株应用于高盐废水的处理, 可实现磷酸盐的有效去除, 具有良好的实际应用价值, 为高盐条件下生物除磷难题的解决提供了一条新的途径。